Knowledge based emergency management information systems: Mapping DERMIS principles - Dorasamy, Magiswary; Raman, Murali; Muthaiyah, Saravanan; Kaliannan, Maniam (2012)
Recent disasters which were composed of major floods and landslides events proved that despite past experiences and strong disaster management mechanism, life and property losses are still unavoidable.Emergency managers need a robust system that can ease the challenges faced. This paper proposes a functional system based on the working principle of The Dynamic Emergency Response Management Information Systems(DERMIS): Design Premise, Conceptual Design, System Specification and Supporting Design Considerations. These four principles are coupled with specific end-user requirements derived from our on-going work. The impact of this study on disaster management is significant to the scientific group within disaster management domain, the government agencies for policy and strategy formulations to preempt, deal with and, ultimately, improve survival rate in disaster.